Development of an Android-based Educational Game Integrating East Kalimantan Local Wisdom to Improve Students’ Mathematical Reasoning - Ryan Angga Pratama (Didaktika: Jurnal Kependidikan, 2026)
This research aims to produce an android educational game based on the local wisdom of East Kalimantan which can improve students’ mathematical reasoning abilities and students can also know, understand, be proud of and love local culture in Indonesia as a form of preserving Indonesian culture, especially in East Kalimantan. The game is called LARIS which is an acronym for “Penalaran Matematis” (in Indonesian) or “Mathematical Reasoning” (in English). Game products were developed by paying attention to aspects of validity, practicality and effectiveness in learning mathematics for class VIII-C students at Patra Dharma 2 Balikpapan Junior High School. The implementation uses the Multimedia Development Life Cycle (MDLC) development design which consists of: concept, design, obtaining content material, assembly, testing, and distribution. There are two types of testing used, namely alpha and beta testing. The alpha test was carried out by 2 learning media experts, 2 learning material and evaluation experts, and 2 learning practitioners. Meanwhile, beta testing was carried out for students twice, namely small and large trials. For the small trial, the subjects were 6 students from class VIII who were chosen randomly, while for the large trial the subjects were 29 students from class VIII-C at Patra Dharma 2 Balikpapan Junior High School. The research results show that the educational game LARIS is included in the very valid category with a percentage of 94.653%, very practical with an average percentage of 88.880%; and effective with a completion percentage reaching 72.413%. So overall the learning media developed can be an alternative in learning activities, especially regarding mathematical reasoning questions.